Severe Aortic Stenosis and Severe Coarctation of the Aorta: A Hybrid Approach to Treatment - McLennan, Daniel; Caputo, Massimo; Taliotis, Demetris (Frontiers in Surgery, 2017)
Hybrid surgery is becoming more popular in the treatment of children with congenital heart disease, particularly small infants and neonates. We report a case of a patient with aortic stenosis (AS) and coarctation of the aorta (CoA). Case: a 1 month old baby presented with severe AS and CoA. The decision was made to perform a hybrid surgical procedure. The patient underwent a lateral thoracotomy for repair of the CoA and carotid cutdown for aortic balloon valvoplasty(AoVP).